TranexAMIC Acid Associated with Less Wound Complications in Hindfoot Surgery. Issue 1 (January 2022) - Moore, Andrew; Smith, Benjamin R.; O'Leary, Ryan J.; Hoch, Caroline P.; Gross, Christopher E.; Scott, Daniel J.
Category: Hindfoot; Ankle Introduction/Purpose: Tranexamic acid (TXA) is an increasingly popular antifibrinolytic therapy used to decrease bleeding during surgery and postoperative swelling. TXA has been shown to decrease bleeding in total knee arthroplasty and total hip arthroplasty, and is now routinely administered in many centers performing these operations. To date, there is very limited data on its use in foot and ankle surgery. We sought to review of the effect of TXA on outcomes of total ankle arthroplasty (TAA), hindfoot fusions, and other related hindfoot surgeries, with the hypothesis that patients receiving TXA would exhibit fewer wound complications. Methods: We conducted a retrospective review of 252 patients (258 operations) undergoing hindfoot fusions and/or TAA between 2015 and 2020 by a single fellowship trained foot and ankle surgeon at an academic medical center. Twenty-seven patients (28 operations) were excluded for less than 90-day follow-up, leaving 230 eligible procedures (TAA=72, subtalar fusion=47, ankle fusion=37, double arthrodesis=33, tibiotalocalcaneal fusion=20, triple arthrodesis=8, total talus=4, and hardware removal=8). Patient demographics, ASA scores, comorbidities, pre-operative diagnoses, smoking status, wound complications, union status (for fusions), readmissions and reoperations were recorded and compared between TXA (n=104) and non-TXA (n=126) cohorts. Subgroup analysis was performed for TAAs and hindfoot fusions. Mean follow-up was 453 days. Continuous variables were compared using independent sample t-test, and categorical variables with chi-square test, unless more than 20% of expected values were less than 5, in which case Fisher's exact tests were utilized. Results: There were no significant differences in demographics, comorbidities, preoperative diagnoses or smoking status between cohorts. The TXA group exhibited significantly less postoperative infections requiring oral antibiotics (5.8% vs. 15.1%, p=.024). These included superficial (p=.174) and deep infections requiring reoperation (p=.095). Subgroup analysis of hindfoot fusions (n=146) revealed significantly shorter time to fusion between TXA and non-TXA groups (146 vs. 202 days, p=.049) and fewer reoperations (8.6% vs. 21.6%, p=.042). TXA fusion patients had significantly shorter follow-up (349 vs. 479 days, p=.020), fewer active smokers (5.2% vs. 15.9%, p=.048), but more patients with Charcot neuroarthropathy (20.7% vs. 5.7%, p=.006). Subgroup analysis of TAAs showed fewer infections requiring oral antibiotics (4.7% vs. 31%, p=.005) and less delayed wound healing (25.6% vs. 48.3%, p=.047) in the TXA cohort. Conclusion: We found TXA use in hindfoot surgery to correlate with a reduction in wound infections requiring antibiotics and quicker time to union in hindfoot fusions. Further, the use of TXA in TAA specifically was correlated with fewer infections requiring antibiotics and lower rates of delayed wound healing. These reductions were both statistically and clinically significant. TXA has already been shown to be beneficial in other areas of orthopaedic surgery and appears to also be quite beneficial in foot and ankle surgery, though further research is needed to confirm these findings.